VARIABEL MAKROEKONOMI TERHADAP INDEKS SAHAM SYARIAH INDONESIA (PERIODE MEI 2011-SEPTEMBER 2015 DENGAN MODEL ECM) - Yudhistira Ardana (MediaTrend, 2016)
This study aimed to analyze the effect of macroeconomic variables on Indonesian Islamic stock index. Macroeconomic variables used is the interest rate of Bank Indonesia (BI-rate), inflation, exchange rate, Bank Indonesia Certificates Sharia (SBIS) and world oil prices. The data used in this research is secondary data during the period May 2011 until September 2015 using a model error correction model (ECM) where the end result is going to measure the effect of macroeconomic variables on Indonesian Sharia Stock Index in the short term and long term.